Loss of deuterium in faecal solids and by sequestration in reindeer: effect on doubly labelled water studies - Gotaas, Geir; Milne, Eric; Haggarty, Paul; Tyler, Nicholas J.C. (Rangifer, 2000)
An underlying assumption when estimating total energy expenditure (TEE) using doubly labelled water (DLW) is that the injected isotopes (lsO and 2H) leave the body only in the form of CO, and H20. However, both isotopes have additional routes of loss. We quantified the loss of 2H (i) attached to faecal solids and (ii) by sequestration into newly synthesised fat in reindeer (Rangifer tarandus tarandus). Estimates of the errors caused by these processes were applied to data from DLW studies with reindeer in summer and in winter. Given the net rate of faecal dry matter output and lipid synthesis in the present study, ignoring both sources of error caused the TEE of reindeer to be underestimated by approximately 5% in winter and approximately 9% in summer. The separate effect of each source of error was evaluated in summer. If ignored, loss of 2H through sequestration alone caused TEE to be underestimated by approximately 3.7%. Similarly, if ignored, loss of 2H attached to faecal solids alone caused TEE to be underestimated by approximately 5.9%.